L’expérience du décrochage scolaire à partir du point de vue de décrocheurs: une étude d’orientation phénoménologique - Ouellet, Alain; Deshaies, Gilles (Canadian Journal of Counselling and Psychotherapy, 2007)
This phenomenological study contributes to enlarging and deepening the understanding of the experience of dropping out of school. By focusing on the experience of the dropouts themselves, the study highlights a number of elements in the process of dropping out of school. The written statements of two dropouts are studied based on a method of phenomenological analysis. The main elements of their experience are then examined in light of the literature devoted to dropping out of school. Suggestions for further research and for the clinical practice of counselling are also presented.